Evaluation of a betavoltaic energy converter supporting scalable modular structure. Issue 2 (12th December 2018) - Kang, Taewook; Kim, Jinjoo; Park, Seongmo; Son, Kwangjae; Park, Kyunghwan; Lee, Jaejin; Kang, Sungweon; Choi, Byoung‐Gun
Abstract : Distinct from conventional energy‐harvesting (EH) technologies, such as the use of photovoltaic, piezoelectric, and thermoelectric effects, betavoltaic energy conversion can consistently generate uniform electric power, independent of environmental variations, and provide a constant output of high DC voltage, even under conditions of ultra‐low‐power EH. It can also dramatically reduce the energy loss incurred in the processes of voltage boosting and regulation. This study realized betavoltaic cells comprised of p‐i‐n junctions based on silicon carbide, fabricated through a customized semiconductor recipe, and a Ni foil plated with a Ni‐63 radioisotope. The betavoltaic energy converter (BEC) includes an array of 16 parallel‐connected betavoltaic cells. Experimental results demonstrate that the series and parallel connections of two BECs result in an open‐circuit voltage V oc of 3.06 V with a short‐circuit current I sc of 48.5 nA, and a V oc of 1.50 V with an I sc of 92.6 nA, respectively. The capacitor charging efficiency in terms of the current generated from the two series‐connected BECs was measured to be approximately 90.7%.